New mutations in BBS genes in small consanguineous families with Bardet-Biedl syndrome: Detection of candidate regions by homozygosity mapping - Pereiro, Ines (Molecular Vision, 2010)
PURPOSE: Bardet-Biedl syndrome (BBS, OMIM 209900) is a rare multi-organ disorder in which BBS patients manifest a variable phenotype that includes retinal dystrophy, polydactyly, mental delay, obesity, and also reproductive tract and renal abnormalities. Mutations in 14 genes (BBS1–BBS14) are found in 70% of the patients, indicating that additional mutations in known and new BBS genes remain to be identified. Therefore, the molecular diagnosis of this complex disorder is a challenging task. METHODS: In this study we show the use of the genome-wide homozygosity mapping strategy in the mutation detection of nine Caucasian BBS families, eight of them consanguineous and one from the same geographic area with no proven consanguinity. RESULTS: We identified the disease-causing mutation in six of the families studied, five of which had novel sequence variants in BBS3, BBS6, and BBS12. This is the first null mutation reported in BBS3. Furthermore, this approach defined homozygous candidate regions that could harbor potential candidate genes for BBS in three of the families. CONCLUSIONS: These findings further underline the importance of homozygosity mapping as a useful technology for diagnosis in small consanguineous families with a complex disease like BBS.